Weak measurement of the optical polarization, chirality and orbital angular momentum via metasurface with polarization filtering. (4th September 2020) - Li, Guang; Shi, Peng
Abstract: We propose a metasurface to evaluate the polarization, chirality and orbital angular momentum of the incident light. By employing the weak measurement mechanism, an aperture with a set orientation is utilized to filter the incident polarization components and enhance the polarization contrast. We demonstrate theoretically and numerically that the mechanism can detect the weak quantities of the incident field by evaluating the orientation angle of the azimuthal polarized component in the back focal plane or imaging plane. Using the aperture as the cell of metasurface, the enhancement can also be realized in the imaging plane. Moreover, by constructing a phase gradient through a couple of mirror symmetric apertures in the cell, the metasurface can produce orbit induced rotation in the imaging plane. Our results could find wide application in the polarization, chirality detection and orbital angular momentum communications.